Progesterone neuroprotection in the Wobbler mouse, a genetic model of spinal cord motor neuron disease - Gonzalez Deniselle, Maria Claudia (2002)
Motor neuron degeneration characterizes the spinal cord of patients with amyotrophic lateral sclerosis and the Wobbler mouse mutant. Considering that progesterone (PROG) provides neuroprotection in experimental ischemia and injury, its potential role in neurodegeneration was studied in the murine model. Two-month-old symptomatic Wobbler mice were left untreated or received sc a 20-mg PROG implant for 15 days. Both light and electron microscopy of Wobbler mice spinal cord showed severely affected motor neurons with profuse cytoplasmic vacuolation of the endoplasmic reticulum and/or Golgi apparatus and ruptured mitochondria with damaged cristae, a profile indicative of a type II cytoplasmic form of cell death. In contrast to untreated mice, neuropathology was less severe in Wobbler mice receiving PROG; including a reduction of vacuolation and of the number of vacuolated cells and better conservation of the mitochondrial ultrastructure. In biochemical studies, we determined the mRNA for the α3 subunit of Na,K-ATPase, a neuronal enzyme controlling ion fluxes, neurotransmission, membrane potential, and nutrient uptake. In untreated Wobbler mice, mRNA levels in motor neurons were reduced by half compared to controls, whereas PROG treatment of Wobbler mice restored the expression of α3 subunit Na,K-ATPase mRNA. Therefore, PROG was able to rescue motor neurons from degeneration, based on recovery of histopathological abnormalities and of mRNA levels of the sodium pump. However, because the gene mutation in Wobbler mice is still unknown, further studies are needed to unveil the action of PROG and the mechanism of neuronal death in this genetic model of neurodegeneration.